Analgesic effects of intravenous ketamine after spinal anaesthesia for non-elective caesarean delivery: a randomised controlled trial - Prahlad Adhikari; Asish Subedi; Birendra Prasad Sah; Krishna Pokharel (BMJ Open)
Objectives This study aimed to determine if low dose intravenous ketamine is effective in reducing opioid use and pain after non-elective caesarean delivery.Design Prospective, randomised, double-blind.Setting Tertiary hospital, Bisheshwar Prasad Koirala Institute of Health Sciences, Dharan, NepalParticipants 80 patients undergoing non-elective caesarean section with spinal anaesthesia.Interventions Patients were allocated in 1:1 ratio to receive either intravenous ketamine 0.25 mg/kg or normal saline before the skin incision.Primary and secondary outcome measures The primary outcome was the total amount of morphine equivalents needed up to postoperative 24 hours. Secondary outcome measures were postoperative pain scores, time to the first perception of pain, maternal adverse effects (nausea, vomiting, hypotension, shivering, diplopia, nystagmus, hallucination) and neonatal Apgar score at 1 and 5 min, neonatal respiratory depression and neonatal intensive-care referral.Results The median (range) cumulative morphine consumption during the first 24 hours of surgery was 0 (0–4.67) mg in ketamine group and 1 (0–6) mg in saline group (p=0.003). The median (range) time to the first perception of pain was 6 (1–12) hours and 2 (0.5–6) hours in ketamine and saline group, respectively (p<0.001). A significant reduction in postoperative pain scores was observed only at 2 hours and 6 hours in the ketamine group compared with placebo group (p<0.05). Maternal adverse effects and neonatal outcomes were comparable between the two groups.Conclusions Intravenous administration of low dose ketamine before surgical incision significantly reduced the opioid requirement in the first 24 hours in patients undergoing non-elective caesarean delivery.Trial registration number NCT03450499.